Letter from the Academy of Natural Sciences to James Curtis Booth - Academy of Natural Sciences of Philadelphia (1837)
James Curtis Booth (1810-1888) is elected a member of the Academy of Natural Sciences of Philadelphia.
Keywords: Booth, James Curtis, 1810-1888; Academy of Natural Sciences of Philadelphia; Natural history--Societies, etc.; Private clubs; Membership requirements